2014
DOI: 10.1186/1471-2105-15-327
|View full text |Cite
|
Sign up to set email alerts
|

tigaR: integrative significance analysis of temporal differential gene expression induced by genomic abnormalities

Abstract: BackgroundTo determine which changes in the host cell genome are crucial for cervical carcinogenesis, a longitudinal in vitro model system of HPV-transformed keratinocytes was profiled in a genome-wide manner. Four cell lines affected with either HPV16 or HPV18 were assayed at 8 sequential time points for gene expression (mRNA) and gene copy number (DNA) using high-resolution microarrays. Available methods for temporal differential expression analysis are not designed for integrative genomic studies.ResultsHer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Besides studying the effect of copy number aberrations on gene expression, the tigaR framework also proved suitable for the identification of temporal miRNA-mRNA interactions [17]. Opposed to BRWD3 and PLXNB2 being downregulated upon overexpression of their validated miRNA interaction partner, FOS expression increased upon miR-221-3p overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides studying the effect of copy number aberrations on gene expression, the tigaR framework also proved suitable for the identification of temporal miRNA-mRNA interactions [17]. Opposed to BRWD3 and PLXNB2 being downregulated upon overexpression of their validated miRNA interaction partner, FOS expression increased upon miR-221-3p overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there was no change in PCNA levels upon PITX2 overexpression, increased levels of CDKN1B and cleaved CASP3 suggested that reduced cell viability in PITX2 overexpressing cells is associated to both cell cycle arrest and apoptosis ( Figure 3d). method, a model without (red continuous line) and with copy number effect (blue discontinuous line) was fitted [17]. Similarity between the fitted models indicates that differential PITX2 expression is not copy number-driven.…”
Section: Tgf-beta Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the chromosomal location DNA copy number transcripts are matched to the mRNA expression features (employing the overlapPlus matching procedure of the sigaR package, van Wieringen et al., ). The miRNA transcripts are a selection on the basis of temporal differential expression (determined using the method of Miok et al., ), that are either up‐ or downregulated in at least three out of four cell lines. Both mRNA gene expression and DNA copy number data then comprise p=64 genes, while the miRNA gene expression data includes q=106 genes, all measured at T=8 time points in n=4 cell lines.…”
Section: Methodsmentioning
confidence: 99%